Correction functions of equilibrium for children with the spastic forms of cerebral paralysis - Zelezniy M.N (Kharkov National Pedagogical University, 2012)
The state of research question correction function of equilibrium is examined for children, patients with a cerebral paralysis. On the basis research of scientific labours the analysis methods and facilities of correction, which are used in the process of their physical rehabilitation, is carried out. It is shown that a process of correction function equilibrium for children with a cerebral paralysis must be sent to development of ability arbitrarily to weaken a skeletal and respiratory musculature, forming of the new corporal feeling and coordination of motions. The aim of article is to research a state of question of correction of function of equilibrium at children with spastic forms of cerebral paralysis at modern stage.